Biallelic COX10 Mutations and PMP22 Deletion in a Family With Leigh Syndrome and Hereditary Neuropathy With Liability to Pressure Palsy. (27th October 2022) - Kuroha, Yasuko; Ishiguro, Takanobu; Tada, Mari; Hara, Norikazu; Murayama, Kei; Kawachi, Izumi; Kasuga, Kensaku; Miyashita, Akinori; Hasegawa, Arika; Takahashi, Tetsuya; Matsubara, Nae; Onodera, Osamu; et al.
Abstract : Objectives: Leigh syndrome is a progressive encephalopathy characterized by symmetrical lesions in brain. This study aimed to investigate the clinicopathologic and genetic characteristics of a family with Leigh syndrome and hereditary neuropathy with liability to pressure palsy (HNPP). Methods: Data from a Japanese family's clinical features, MRIs, muscle biopsy, and an autopsy were analyzed. A whole-exome sequence was performed, as well as real-time PCR analysis to determine copy number variations and Western blot analyses. Results: The proband and her 2 siblings developed spastic paraplegia and mental retardation during childhood. The proband and her sister had peripheral neuropathy, whereas their father developed compression neuropathy. Leigh encephalopathy was diagnosed neuropathologically. Brain MRI revealed changes in cerebral white matter as well as multiple lesions in the brainstem and cerebellum. Muscle biopsy revealed type 2 fiber uniformity and decreased staining of cytochrome c oxidase. The COX10 missense mutation was identified through whole-exome sequence. A 1.4-Mb genomic deletion extending from intron 5 of COX10 to PMP22 was detected. Discussion: These findings suggest that in this family, Leigh syndrome is associated with a mitochondrial respiratory chain complex IV deficiency caused by biallelic COX10 mutations coexisting with HNPP caused by heterozygous PMP22 deletion.